(untitled) (Journal of Dhaka Medical College, 2010)
Background: Acute promyelocytic leukemia (APL), is now curable in most cases with current treatment strategies. But limited available data suggest that the rate of early mortality is high and long term survival is poor in many developing countries. To improve the survival rate by reducing early mortality, study of the status of early mortality as the main cause of treatment failure for the management of APL as a heamatological emergency appears to have a great significance. Materials and method: Diagnosis of acute promyelocytic leukemia was done from bone marrow morphological study by experienced haematologist. After that cytogenetic study to see chromosomal translocation 15 and 17 and molecular study to see PML-RARá fusion protein was also done. Clinical and laboratory evaluation was done to all of them. Chemotherapy according to IC-APL protocol was given to 30 out of 40 patients. Incidence of early mortality (death within 14 days of diagnosis) was recorded and also categorized according to cause of death. Pattern of supportive cares given to the patients such as management of coagulopathy. ATRA syndrome or sepsis to treat the disease as a medical emergency was also recorded. Result: Selected clinical, laboratory and outcome data of 40 cases of APL who were admitted in Haematology department of BSMMU was surveyed. The median age overall was 32 yrs. The median WBC count at diagnosis was 7.75×109/L and median platelet count 25×109/L. Laboratory evidence of DIC was noted in 37.5% of patients. Death occurred within 14 days of diagnosis (early death) in 10 (25%) cases. Bleeding was the most common cause of early death, then infectious complication and ATRA syndrome. Among 30 patients who got chemotherapy complete remission (CR) was 66.6%. So only 50% of the total study population was able to achieve CR. So due to early mortality, a significant portion of the study population could not receive protocol based treatment. Conclusion: To improve outcome by reducing initial mortality early recognition and treatment of APL is required in specialized institutions, by prompt and aggressive supportive therapy as well as immediate starting of antileukemic agent such as ATRA, arsenic trioxide etc. Key words: Acute Promyelocytic Leukaemia (APL); mortality. DOI: 10.3329/jdmc.v18i2.6277 J Dhaka Med Coll. 2009; 18(2) : 150-154